Fisetin Prevents HT22 Cells From High Glucose-Induced Neurotoxicity via PI3K/Akt/CREB Signaling Pathway - Zhang, Shenshen; Xue, Ran; Geng, Yaping; Wang, Hao; Li, Wenjie (Frontiers in Neuroscience, 2020)
Hyperglycemia has been widely considered as a key risk factor for diabetic encephalopathy which can cause neuronal apoptosis and cognitive deficits. The flavonoid compound, fisetin, possesses potential neuroprotective effects and also enhances learning and memory. However, the role of fisetin in hyperglycemia-induced neuronal cytotoxicity has not been fully elucidated. In the present study, HT22 murine hippocampal neuronal cell line was used to establish the injured cell model. Cell proliferation and cytotoxicity assay, hoechst 33258 staining, qRT-PCR, western blot analysis, and specific inhibitor was used to investigate the effect and molecular mechanisms of fisetin on high glucose (HG)-induced neurotoxicity in HT22 cells. Our results showed that 125 μM and 48 h of treatment was identified as optimal damage parameter of HG. Fisetin significantly improved HG-inhibited cell viability. The levels of LDH, MDA and SOD were noticeably modulated by fisetin, which alleviated HG-induced HT22 cell oxidative damage. Besides, the apoptosis of HT22 cells was rescued by fisetin pretreatment. In addition, fisetin also prevented HG-induced downregulation of the mRNA expression of Bdnf, Gdnf, Syp (Synaptophysin) and Gria1 (Glutamate Ionotropic Receptor AMPA Type Subunit 1) in cells. More importantly, the decreased phosphorylation of PI3K, Akt and CREB was rescued by fisetin treatment and that neuroprotective effect of fisetin was partially blocked by PI3K inhibitor, LY294002. These findings indicate that fisetin has potent neuroprotective effect and prevents HG-induced neurotoxicity by activation of PI3K/Akt/CREB pathway.